Impact of a Hemoglobin Trigger Communication Tool on Perioperative Transfusion in Cardiac Surgery. Issue 9 (September 2022) - Fouda, Eslam A.; Narciso, Patricia; Renew, J. Ross; Porter, Steven B.; Rodrigues, Eduardo S.
Abstract : Blood transfusion strategies in cardiac surgeries have been subject to multiple studies to avoid the hazards associated with blood product transfusion while maintaining safe outcomes. This article investigates the effect of implementing a verbal hemoglobin trigger in the surgical timeout on perioperative transfusion in cardiac surgery. Abstract: Objectives: Blood transfusion represents an important and potentially modifiable risk in the daily practice of cardiac surgery. The risk profile and increasing cost of transfusion led us to study the effect of different maneuvers, interventions, or surgical techniques to minimize transfusion while maintaining patient safety. This study compares postoperative outcomes before and after incorporating a verbal hemoglobin (Hb) trigger during the surgical timeout in which the surgeon and anesthesiologist preemptively agree on a threshold for packed red blood cell (PRBC) administration in the perioperative period. Methods: The authors performed a chart review of patients who underwent cardiac surgery from July 2013 through June 2014 at our institution. Patients who underwent surgery from July 2013 through December 2013 served as the pre-Hb trigger group, and patients who underwent surgery from January 2014 through June 2014 served as the post-Hb trigger group. Information collected included patient demographics, type of cardiac surgery, preoperative Hb, Hb trigger, and intraoperative and postoperative variables. The primary outcome was the incidence of PRBC transfusions. Secondary outcomes included the incidence of frozen plasma (FP) transfusion, mechanical ventilation beyond postoperative day 1, and 30-day mortality. Results: The study included 191 patients, with 84 in the pre-Hb trigger group and 107 in the post-Hb trigger group. Intraoperative PRBC transfusions did not decrease in the posttrigger group compared with the pretrigger group (pretrigger 51.4% vs posttrigger 52.4%, P = 1.0); however, intraoperative FP administration was lower in the posttrigger group (65.4% vs 50.0%, P = 0.038). Postoperative mechanical ventilation beyond postoperative day 1 also was significantly lower in the posttrigger group compared with the pretrigger group (27.1% vs 14.3%, P = 0.035). Conclusions: Implementation of a verbal Hb trigger during the surgical timeout was associated with a reduction in FP administration and duration of mechanical ventilation, but not a decrease in PRBC transfusion and mortality.